2020
DOI: 10.1038/s41598-020-62550-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarkers from cell-based assays for AhRL and MIS strongly predicted the future development of diabetes in a large community-based prospective study in Korea

Abstract: exposure to environment-polluting chemicals (epc) is associated with the development of diabetes. Many EPCs exert toxic effects via aryl hydrocarbon receptor (AhR) and/or mitochondrial inhibition. Here we investigated if the levels of human exposure to a mixture of EPC and/or mitochondrial inhibitors could predict the development of diabetes in a prospective study, the Korean Genome and epidemiological Study (KoGeS). We analysed AhR ligands (AhRL) and mitochondria-inhibiting substances (MiS) in serum samples (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 47 publications
(50 reference statements)
4
22
0
Order By: Relevance
“…This fact, coupled with the small size of our sample, limits the strength of our overall findings. Nonetheless, being prospective in nature and with findings similar to those recently reported in a Korean cohort [11], our study presents important evidence to support a causal role of these pollutants in the current diabetes pandemic.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This fact, coupled with the small size of our sample, limits the strength of our overall findings. Nonetheless, being prospective in nature and with findings similar to those recently reported in a Korean cohort [11], our study presents important evidence to support a causal role of these pollutants in the current diabetes pandemic.…”
Section: Discussionsupporting
confidence: 88%
“…Following this reasoning, the presence of POPs such as dioxins, not present during the evolution of these cellular mechanisms, may produce a pathological disruption of metabolism involving both insulin resistance and beta cell decline, apparently partially mediated by the AhR and at least partially the result of mitochondrial dysfunction. Our data, together with others [5,11,30], who have used the same cell-based assays here employed provide epidemiologic evidence produced in free-living populations which validates previous basic science and clinical research on the role of mitochondrial dysfunction in the pathophysiology of diabetes [5,7,25,26,29,30], especially in the presence of greater AhR activation, thus strengthening the contention that POPs cause diabetes and providing a causal pathway for their action.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Interestingly, a meta-analysis showed that the antihyperglycemic drug metformin, which also displays antiinflammatory properties, has benefits in both prevention and treatment outcomes of TB patients with diabetes (Cameron et al, 2016;Zhang and He, 2020). Paradoxically, serum AhR ligand activity was higher in subjects with Type II diabetes, correlated with parameters of insulin resistance, and was a risk factor for diabetic nephropathy (Kim et al, 2013;Roh et al, 2015;Lee et al, 2020). The authors attributed AhR ligand activity to persistent organic pollutants such as tetrachlorodibenzo-para-dioxin, a dioxin with the highest known binding affinity to AhR (Mandal, 2005), although a causal relationship was not established.…”
Section: Ipa For Tb-diabetes?mentioning
confidence: 99%